The multiple meanings of "wheezing": a questionnaire survey in Portuguese for parents and health professionals - Fernandes Ricardo M; Robalo Brígida; Calado Cláudia; Medeiros Susana; Saianda Ana; Figueira Joana; Rodrigues Rui; Bastardo Cristina; Bandeira Teresa (BMC, 2011)
Abstract Background Most epidemiological studies on pediatric asthma rely on the report of "wheezing" in questionnaires. Our aim was to investigate the understanding of this term by parents and health professionals. Methods A cross-sectional survey was carried out in hospital and community settings within the south of Portugal. Parents or caregivers self-completed a written questionnaire with information on social characteristics and respiratory history. Multiple choice questions assessed their understanding of "wheezing". Health professionals (physicians, nurses and physiotherapists) were given an adapted version. We used bivariate analysis and multivariate models to study associations between definitions of "wheezing" and participants' characteristics. Results Questionnaires from 425 parents and 299 health professionals were included. The term "wheezing" was not recognized by 34% of parents, more frequently those who were younger (OR 0.4 per 10-year increment, 95% CI 0.3-0.7), had lower education (OR 3.3, 95% CI 1.5-7.4), and whose children had no history of respiratory disease (OR 4.6, 95% CI 2.5-8.7) (all ORs adjusted). 31% of parents familiar with "wheezing" either did not identify it as a sound, or did not locate it to the chest, while tactile (40%) and visual (34%) cues to identify "wheezing" were frequently used. Nurses reported using visual stimuli and overall assessments more often than physicians (p < 0.01). The geographical location was independently associated with how parents recognized and described "wheezing". Conclusions Different meanings for "wheezing" are recognized in Portuguese language and may be influenced by education, respiratory history and regional terminology. These findings are likely applicable to other non-English languages, and suggest the need for more accurate questionnaires and additional objective measurement instruments to study the epidemiology of wheezing disorders.